The Use of Eleven Translation Techniques in Translating a Webtoon Comic by Dito Satrio Suryonugroho Entitled ‘Jajan Squad’ - Rizka Putri Edianza; Artika Wina Fitriani (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
This article is the activities collected Indonesian transcript data from the web comic